The genetics of virus particle shape in equine influenza A virus - Elton, Debra; Bruce, Emily A.; Bryant, Neil; Wise, Helen M.; MacRae, Shona; Rash, Adam; Smith, Nikki; Turnbull, Matthew L.; Medcalf, Liz; Daly, Janet M.; Digard, Paul (Wiley, 2013)
Background Many human strains of influenza A virus produce highly pleomorphic virus particles that at the extremes can be approximated as either spheres of around 100 nm diameter or filaments of similar cross-section but elongated to lengths of many microns. The role filamentous virions play in the virus life cycle remains enigmatic.